Evaluation of some Blood levels of Chronic Kidney Diseases Patients In Wasit Province Iraq - Abdul- Sattar AL-Awsi, Nagham; R. S. AL-Attabi, Mohammed (Cuestiones de Fisioterapia, 2024)
Chronic kidney disease (CKD) is a condition of progressive loss of kidney function diagnosed when the estimated glomerular filtration rate (GFR) is less than 60 mL/min/1.73 m2, persisting for three months or longer. Epidemiological updates for 2022 indicate that the current total number of individuals with CKD at stages 1 to 5 worldwide is estimated at 843 million. Risk factors can be identified by studying blood components, where statistically significant differences are found in statistical analysis of some blood parameters (Red blood cells RBC , Hemoglobin Hb, Hematocrit PCV and Sedimentation rate ESR), in addition to decreased production of endogenous Erythropoietin (EPO), a hormone involved in the differentiation and maturation of red blood cells. Other contributing factors have been identified, such as poor bone marrow response to erythropoietin, decreased availability of iron for red blood cell formation, or Vitamin deficiencies (vitamin B12 or folic acid). Furthermore, the kidney is the main regulator. 90 subjects of both genders were collected, including 60 patients and 30 from the control group. The results showed that the level of blood parameters had significant differences compared to the control group at p ≤ (0.05). The studied parameters contribute as indicators of the development of health risks to the body and kidney health in chronic kidney disease patients.